Surgical Management of Vesicoureteral Reflux and Ureteral Strictures in Atypical Ureteral Anatomy: A Narrative Review - Kamińska, Monika; Niemiec, Bartosz; Drozd, Zuzanna; Olesiński, Bruno; Piosik, Szymon; Dudziak, Natalia; Piasecki, Łukasz; Guzowicz, Zuzanna; Gągałka, Patrycja (Journal of Education, Health and Sport, 2026)
Introduction and Objective: Congenital anomalies of the ureter affect 1% of the population and can lead to complications like vesicoureteral reflux (VUR) and ureteral strictures (US). This review aims to summarize current surgical treatments for these conditions, focusing specifically on patients with atypical anatomy, such as ectopic, retrocaval, or duplex ureters. Review Methods: A literature review of PubMed and Scopus databases was conducted, in accordance with the PRISMA guidelines, focusing on English-language papers published within the last five years. Evaluated surgical approaches included open, endoscopic, laparoscopic, and robotic methods. Following the application of specific inclusion and exclusion criteria, a total of 33 articles were selected for qualitative synthesis. Due to the early diagnosis of these anomalies, the analyzed data primarily concerns pediatric patients. Results: Open surgery remains the gold standard for severe VUR, but minimally invasive laparoscopic and robotic options are gaining popularity. For complex congenital anomalies, treatments must be highly customized. Functioning ectopic ureters require reimplantation, while poorly functioning ones are managed with laparoscopic clipping. Retrocaval ureters or duplex systems benefit from advanced robotic repairs. Obstructive megaureters and ureteroceles are initially treated with less invasive endoscopic methods (balloon dilation or incision) to relieve pressure. Summary: The management of VUR and US in patients with complex anatomy lacks a single standard approach, requiring individualization based on specific anatomy and kidney function. While open surgery is effective, urology is shifting toward minimally invasive techniques to lower risks. There is a notable lack of comprehensive literature regarding surgical outcomes in adults and complex congenital presentations.